β2-Adrenergic Receptor Activation Suppresses the Rat Phenethylamine Hallucinogen-Induced Head Twitch Response: Hallucinogen-Induced Excitatory Post-synaptic Potentials as a Potential Substrate - Marek, Gerard J.; Ramos, Brian P. (Frontiers in Pharmacology, 2018)
5-Hydroxytryptamine2A (5-HT2A) receptors are enriched in layers I and Va of the rat prefrontal cortex and neocortex and their activation increases the frequency of glutamatergic excitatory postsynaptic potentials/currents (EPSP/Cs) onto layer V pyramidal cells. A number of other G-protein coupled receptors (GPCRs) are also enriched in cortical layers I and Va and either induce (1-adrenergic and orexin2) or suppress (metabotropic glutamate2 [mGlu2], adenosine A1, -opioid) both 5-HT-induced EPSCs and head twitches or head shakes induced by the phenethylamine hallucinogen 2,5-dimethoxy-4-iodoamphetamine (DOI). Another neurotransmitter receptor also localized to apparent thalamocortical afferents to layers I and Va of the rat prefrontal cortex and neocortex is the 2-adrenergic receptor. Therefore, we conducted preliminary electrophysiological experiments with rat brain slices examining the effects of epinephrine on electrically-evoked EPSPs following bath application of DOI (3 M). Epinephrine (0.3-10 M) suppressed the late EPSPs produced by electrical stimulation and DOI. The selective 2-adrenergic receptor antagonist ICI-118,551 (300 nM) resulted in a rightward shift of the epinephrine concentration-response relationship. We also tested the selective 2-adrenergic receptor agonist clenbuterol and the antagonist ICI-118,551 on DOI-induced head twitches. Clenbuterol (0.3-3 mg/kg, i.p.) suppressed DOI(1.25 mg/kg, i.p.)-induced head twitches. This clenbuterol effect appeared to be at least partially reversed by the selective 2-adrenergic receptor antagonist ICI-118,553 (0.01-1 mg/kg, i.p.), with significant reversal at doses of 0.1 and 1 mg/kg. Thus, 2-adrenergic receptor activation reverses the effects of phenethylamine hallucinogens in the rat prefrontal cortex. While Gi/Go-coupled GPCRs have previously been shown to suppress both the electrophysiological and behavioral effects of 5-HT2A receptor activation in the mPFC, the present work appears to extend this suppressant action to a Gs-coupled GPCR. Furthermore, the modulation of 5-HT2A receptor activation induced glutamate release onto mPFC layer V pyramidal neurons apical dendrites by a range GPCRs in rat brain slices appears to results in behaviorally salient effects of relevance when screening for novel CNS therapeutic drugs.